Macrófitas aquáticas e efluente de cervejaria: dinâmica e perspectivas - Gonzalez, Aline Costa (2015)
In the last decades, environmental problems have become more serious and frequent, especially due to the expansion of industrial activities. Those occupy the second position on total water consumption and generate alteration in its quality because of pollutant release, causing eutrophication and pollution of water resources. Therefore, it is necessary to raise sustainable technologies that praise environmental conservation and the use of natural resources, making possible a more efficient use of water, reducing costs and saving it to different sectors. Thus, having in mind the several benefits as the improvement of water quality, better distribution and rationing of it, allied to water waste treatment required by environmental control agencies, this research aimed to evaluate and to compare the efficiency of two aquatic macrophyte species on the removal of polluting substances from brewery wastewater, in order to provide an alternative technology, which is also clean, efficient, aesthetic and with low energetic costs. An experimental system was carried out in mesocosms with two treatments composed by the species Salvinia molesta and Limnobium laevigatum, with four replicates each one. Each mesocosm was filled with 80 liters of brewery wastewater 25% diluted and 40g of macrophytes. The experiment was conducted during 28 days and the wastewater was weekly sampled to measure limnological characterizes in laboratory. Moreover, macrophytes were weekly weighed, and leaf area was measured to monitor the biomass development. It was possible to observe that both macrophytes species used in this biological treatment were able to clarify wastewater, to eliminate great portion of smell and to significantly reduce the pollutant charge, which parameters, at some point, were in conformity with Brazilian legislation, except for phosphorus. It was also possible to notice that in the first week the removal percentage was quick, but in the second and the third week the variable concentrations analyzed practically were not altered e and started to raise, demonstrating that the macrophytes reached their tolerance limit. Hence, trying to reduce even more the analyzed parameters concentrations, especially for phosphorus, it is suggested that the plants should be replaced in that period. It could be concluded that these macrophytes species have a great potential on pollutant removal and biomass production. So, they are recommendable in biological technologies for the treatment of wastewater, making possible the reuse of the treated water and the biomass.